Benchmarking da produção de leite, avaliado no município de Bambuí-MG - Carmo, William Júnio do (2011)
This paper evaluated the benchmarking of milk production with a survey of data in the state of Minas Gerais and the city of Bambuí, MG. The analysis was performed within an intensive production system with animals on pasture, with the purpose of surveying milk production in Bambuí to establish differences in productivity, competitiveness and sustainability of farms which are benchmarks of the city and state. The data and the samples of the research were submitted to the internal and external benchmarking technique for assaying the variables. Differences of performance in productivity were observed by benchmarking several milk production units in Bambuí and Minas Gerais. In face of the characteristics of the benchmarking units of the city in relation to the state, this study showed that the milk productive chain of the city in relation to the state and the country is economically competitive and sustainable, despite the significant decrease in the number of milk producers in the Bambuí region.